Gimpute: an efficient genetic data imputation pipeline - Chen, Junfang; Lippold, Dietmar; Frank, Josef; Rayner, William; Meyer-Lindenberg, Andreas; Schwarz, Emanuel (Bioinformatics, 2018)
Genotype imputation is essential for genome-wide association studies (GWAS) to retrieve information of untyped variants and facilitate comp